2017
DOI: 10.1080/1061186x.2016.1278219
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized anionic guanidinylated O-carboxymethyl chitosan/N-2-hydroxypropyltimehyl ammonium chloride chitosan nanoparticles for siRNA pulmonary delivery: preparation, characterization and in vitro evaluation

Abstract: This study developed a pH-sensitive anionic system composed of guanidinylated O-carboxymethyl chitosan (GOCMCS) and N-2-hydroxypropyltimehyl ammonium chloride chitosan (N-2-HACC) for efficient siRNA delivery to the lungs following nebulization. About 16.8% of guanidine groups were incorporated into O-carboxymethyl chitosan (OCMCS) with the aid of O-methylisourea. Gel electrophoresis images demonstrated that siRNA was successfully encapsulated in nanoparticles ranging from 150 to 180 nm with zeta potential of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…As almost all endocytic pathways are energy-dependent processes, they can be inhibited by low temperature incubation or ATP depletion [56, 57]. To analyze the energy-dependent endocytosis pathway, we used 4 °C for the treatment because cells consume less ATP and block the active transport at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…As almost all endocytic pathways are energy-dependent processes, they can be inhibited by low temperature incubation or ATP depletion [56, 57]. To analyze the energy-dependent endocytosis pathway, we used 4 °C for the treatment because cells consume less ATP and block the active transport at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by reports indicating that amphoteric polymers have better transfection efficiency compared with their cationic analogs because of their enhanced pH buffering properties. It is hypothesized that polymeric buffers consume endosomal protons and, therefore, derive endosomal proton-chloride co-transporter to keep shuttling protons and chloride ions into endosomes leading to increased osmotic pressure, endosomal swelling, and eventually endosomal rupture and escape of siRNA cargo into the cellular cytoplasm (Oskuee et al, 2009 ; Richard et al, 2013 ; Ni et al, 2017 ; Ryu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of the study, we selected CS nanoparticles as a delivery vector for 5-FU and siRNA, which has been widely used as gene carrier. 35,36 Following this, an evaluation of the properties of the nanoparticles was conducted, including entrapment efficiency, particle size and zeta potential. The binding efficiency of CS nanoparticles and siRNA was evaluated by agarose gel electrophoresis and the results obtained showed that CS nanoparticles can effectively bind siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, we selected CS nanoparticles as a delivery vector for 5-FU and siRNA, which has been widely used as gene carrier 35,36. (A) The accumulation of Rho-123 in cells.…”
mentioning
confidence: 99%